Development of Higher Order Thinking Skill Qualified Test on Colligative Properties of Solutions - Rahielanamy Rahielanamy*; Agus Kamaludin (Jurnal Pendidikan Sains Indonesia, 2022)
Higher-order thinking skills (HOTS) become one of the major focuses of 21st-century learning. Those skills can be trained through stimulus in the learning process and assessment that uses hots-based questions. The research aims to generate higher-order thinking skills qualified questions on colligative properties of solutions that fulfill validity and reliability instrument. This research uses the Borg Gall development model that consists of data collection, product planning, expert validation, limited trial, and final product improvement stages. The data collection procedure consisted of a study of documentation, validation sheets, and tests. Validation sheets are used to carry out validation tests and product quality assessments by experts and reviewers. The test was used to conduct a limited trial by 40 students of class XII MAN Temanggung. The test subjects were selected using a purposive sampling technique. The results of this study were 20 HOTS-qualified multiple-choice questions on the colligative properties of solutions that have very good quality by the experts and reviewers' judgment. Item analysis based on the results of the limited test on 40 students showed 17 items (85%) were valid with a reliability value of 0.82 (very strong); the difficulty level of the items is 15% easy, 75% medium, 10% difficult and; the distinguishing power of questions obtained 85% good categories. It can be concluded that the HOTS-qualified questions for the material of Colligative Properties of Solutions have good quality and are suitable for use as an assessment instrument